The arrangement of medical records in implementation of Telemedicine in Hospitals - Pakendek, Adriana; Warka, Made; Hufron, Hufron; Mangesti, Yovita Arie (Technium Social Sciences Journal, 2022)
Legal research methods are procedures or steps that are considered effective and efficient. Based on the discussion, it is concluded as follows 1)The legal principles of hospital telemedicine include prprinciples of Information and Communication Technology (ICT) utilization, the principle of state and community responsibility, the principle of competence, integrity, and quality, the principle of equality, good faith, independence, and volunteerism as well as legal certainty and the principle of data security and confidentiality as well as standardization, the principle of patient autonomy and freedom to choose technology or technology neutral and the principle of patient interest is prioritized, data protection, IT forensics, best practices, and legal audit standards as well as justice and legal protection principles 2) medical record regulation different countries, namely Indonesia and America. Indonesia does not yet have a law that specifically regulates electronic medical records. Apart from the ITE Law.